2016
DOI: 10.1002/adfm.201603607
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Confinement Pyrolysis Transformation of ZIF‐8 to Nitrogen‐Enriched Meso‐Microporous Carbon Frameworks for Oxygen Reduction

Abstract: Metal organic framework (MOF)‐derived nitrogen‐enriched nanocarbons have been proposed as promising metal‐free electrocatalysts for oxygen reduction reaction. However, the characteristic microporous feature of MOF‐derived carbon determined by the MOF structure significantly hinders the mass transfer and exposure of active sites, resulting in unsatisfactory electrocatalytic performance. Here an in situ confinement pyrolysis strategy that can simply but efficiently transform monodisperse ZIF‐8 polyhedrons to nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
187
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 293 publications
(196 citation statements)
references
References 37 publications
1
187
0
Order By: Relevance
“…[58,60] For instance, in order to fabricate N-doped MOF-derived materials, zeolitic imiazolate frameworks (ZIFs), a subclass of MOFs composed of tetrahedrally coordinated transition metal ions (e.g., Zn, Fe, Co, Cu) and imidazolate (IM) ligands, are frequently utilized as the precursor and/or template because of their high N content and other preferred properties, such as large surface area and uniform particle size. [24,33,34,36,[38][39][40][41]44,53,[64][65][66][67][68][69] Recently, You et al reported the conversion of ZIF-67 (Co(MIM) 2 , MIM = methylimidazole) to Co-and N-doped carbon (CoNC) via direct pyrolysis, producing a N-doped material with high N content. [39] Similarly, Chen and co-workers studied porous carbon materials derived from a series of bimetallic ZIFs (BMZIFs), which are based on ZIF-8 and ZIF-67 with varied Zn/Co ratio.…”
Section: Nitrogen Dopingmentioning
confidence: 99%
See 4 more Smart Citations
“…[58,60] For instance, in order to fabricate N-doped MOF-derived materials, zeolitic imiazolate frameworks (ZIFs), a subclass of MOFs composed of tetrahedrally coordinated transition metal ions (e.g., Zn, Fe, Co, Cu) and imidazolate (IM) ligands, are frequently utilized as the precursor and/or template because of their high N content and other preferred properties, such as large surface area and uniform particle size. [24,33,34,36,[38][39][40][41]44,53,[64][65][66][67][68][69] Recently, You et al reported the conversion of ZIF-67 (Co(MIM) 2 , MIM = methylimidazole) to Co-and N-doped carbon (CoNC) via direct pyrolysis, producing a N-doped material with high N content. [39] Similarly, Chen and co-workers studied porous carbon materials derived from a series of bimetallic ZIFs (BMZIFs), which are based on ZIF-8 and ZIF-67 with varied Zn/Co ratio.…”
Section: Nitrogen Dopingmentioning
confidence: 99%
“…[40b, 41,67f ] As expected, heteroatom-doped carbon materials have emerged as a new class of advanced metalfree electrocatalysts, due to their extraordinary electrocatalytic performance, better defined reaction mechanisms, low cost, simple preparation, and easy scale-up. [33,[56][57][58][59][60][61][62][63] www.advancedsciencenews.com Among the single heteroatom-doped carbon materials, one of the most widely studied cases is the substitution of partial C (χ = 2.55) with more electronegative N (χ = 3.04). [33,56,58,60,63] In particular, MOF precursors with N-containing ligands can be directly converted into N-doped electrocatalysts after pyrolysis under inert atmosphere.…”
Section: Nitrogen Dopingmentioning
confidence: 99%
See 3 more Smart Citations